C1 domain: investigation of Diacylglycerol/Phorbol ester binding properties and development of ligands - Borah, Rituparna (My University, 2016)
C1 domain is well known for its’ vital role in cell signaling. The localization of different kinase proteins to the cellular membrane through the interaction of their C1 domain with DAG regulates different cell signaling processes. It has already been reported that C1 domain mediated cell signaling is widely involved in progression of cancer, Alzheimer’s diseases and others. Therefore it has been considered as an attractive therapeutical target. Here we have chosen two C1 domain containing protein- Protein Kinase C (PKC) and Myotonic Dystrophy Kinase related CDC42 binding kinase (MRCK). The introductory chapter (Chapter 1) describes the role of C1 domain in different diseases, structure, function and regulation of C1 domain and a brief summary of C1 domain ligands. The C1 domain of PKC is most widely studied till now. Tremendous efforts are underway for the development of PKC activators. The activity of PKC isozymes is also regulated by the biophysical properties of membrane.
Manna, Debasis
Keywords: CHEMISTRY